Implementasi Ekstrakurikuler Pramuka Terhadap Sikap Disiplin Siswa di SMP N 1 Tambusai Utara: Ekstrakurikuler Pramuka, Disiplin - Hariyanto; Putra, Muarif Arhas; Manurizal, Lolia (Journal Of Sport Education and Training, 2022)
This study aims to find out how the concepts, activities and roles of the Scout movement to form Discipline Attitudes in class VIII students of SMP Negeri 1 Tambusai Utara. This type of research is descriptive quantitative which aims to describe or describe something, such as conditions, situations, events and activities. Using the survey method. The population in this study were all scouting extracurricular participants at SMP Negeri 1 Tambusai Utara consisting of 137 grade VIII students. The total sampling in this study was 137 people. This research was conducted on July 16-17, 2021, at SMP Negeri 1 Tambusai Utara. Collecting data using a questionnaire and the data were analyzed descriptively. Based on the results of data analysis and discussion. So it can be concluded that the positive and significant influence between scout extracurriculars on the discipline attitude of students of SMP Negeri 1 Tambusai Utara, was included in the "very strong" category with an average percentage gain of 88.16%, and scout extracurricular was an activity that has a positive impact in shaping student discipline. The conclusion of this study was that it is included in the "very strong" category with an average percentage of 88.16%, and scout extracurricular activities are activities that have a positive impact in shaping student discipline.